2021
DOI: 10.1111/and.13986
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new biomarkers in immune microenvironment of testicular germ cell tumour

Abstract: To seek novel prognostic biomarkers for testicular germ cell tumour (TGCT) and investigate the tumour immune microenvironment, we identified critical differentially expressed genes (DEGs) by overlapping GSE1818 dataset from Gene Expression Omnibus (GEO). Protein–protein interaction (PPI) network was used to investigate key modules and hub genes. Functional enrichment analysis was performed to investigate the underlying molecular functions of the DEGs in TGCT development and progression. The following survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…These results show that SPA17 plays an essential role in predicting the prognosis of cancer patients and is expected to become a powerful biomarker of prognosis for cancer patients. Thus, some of our results are consistent with the conclusion of a previous study ( 32 ), making our results more reliable.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results show that SPA17 plays an essential role in predicting the prognosis of cancer patients and is expected to become a powerful biomarker of prognosis for cancer patients. Thus, some of our results are consistent with the conclusion of a previous study ( 32 ), making our results more reliable.…”
Section: Discussionsupporting
confidence: 93%
“…Notably, in TGCT, the SPA17 expression was significantly inhibited. This may be related to its ligand Ropporin, a spermatogenic cell-specific protein, which has also been confirmed in previous studies ( 31 , 32 ). The results indicated that SPA17 expression was unbalanced in cancers, consistent with previous studies.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Even with so many immune cells infiltrating the tumour, immune escape is made possible by mechanisms like an enhanced PD-L1 expression, WNT/β-catenin pathway (T cell infiltration inhibition), FasL expression (pro-apoptotic signal for tumour infiltrating lymphocytes or TILs) and androgen receptor erasure in Sertoli cells [ 110 ]. This interest in the EMT of TGCT has led to an increased search for prognostic and diagnostic biomarkers, as described by Song et al in their recent bioinformatic analysis [ 113 ].…”
Section: Cancer and Inflammationmentioning
confidence: 99%
“…While tumor-infiltrating T-lymphocytes have been attributed to the development of malignant extracranial GCT [15], PD-L1 + tumor-associated macrophages (TAM) have been detected rather in seminomas than nonseminomas [16]. Additionally, analysis of 22 types of tumor-infiltrating immune cells revealed high infiltration of CD8+ T-cells, macrophages, and dendritic cells in GCTs compared with normal samples [17]. In other tumor entities, such as pancreatic ductal adenocarcinoma, colorectal adenocarcinoma, or prostate cancer, highly differentiated and activated fibroblasts (cancerassociated fibroblasts; CAF) were demonstrated to enhance tumor proliferation and metastatic capacity [18][19][20][21], while inhibiting vascular-like network formation [19].…”
Section: Introductionmentioning
confidence: 99%